Effects of trans‐Eurasian transport of air pollutants on surface ozone concentrations over Western China. Issue 21 (6th November 2014) - Li, Xiaoyuan; Liu, Junfeng; Mauzerall, Denise L.; Emmons, Louisa K.; Walters, Stacy; Horowitz, Larry W.; Tao, Shu
Abstract: Due to a lack of industrialization in Western China, surface air there was, until recently, believed to be relatively unpolluted. However, recent measurements and modeling studies have found high levels of ozone (O3 ) there. Based on the state‐of‐the‐science global chemical transport model MOZART‐4, we identify the origin, pathway, and mechanism of trans‐Eurasian transport of air pollutants to Western China in 2000. MOZART‐4 generally simulates well the observed surface O3 over inland areas of China. Simulations find surface ozone concentrations over Western China on average to be about 10 ppbv higher than Eastern China. Using sensitivity studies, we find that anthropogenic emissions from all Eurasian regions except China contribute 10–15 ppbv surface O3 over Western China, superimposed upon a 35–40 ppbv natural background. Transport from European anthropogenic sources to Northwestern China results in 2–6 ppbv O3 enhancements in spring and summer. Indian anthropogenic sources strongly influence O3 over the Tibetan Plateau during the summer monsoon. Transport of O3 originating from emissions in the Middle East occasionally reach Western China and increase surface ozone there by about 1–4 ppbv. These influences are of similar magnitude as trans‐Pacific and transatlantic transport of O3 and its precursors, indicating the significance of trans‐Eurasian ozone transport in hemispheric transport of air pollution. Our study further indicates that mitigation of anthropogenic emissions from Europe, the Indian subcontinent, and the Middle East could benefit public health and agricultural productivity in Western China. Key Points: Western China has higher surface O3 concentrations compared with Eastern China Foreign Eurasian emissions contribute 10–15 ppbv surface O3 over Western China Mitigation of emissions from EU and IN could benefit public health in Western China